1997
DOI: 10.1364/oe.1.000391
|View full text |Cite
|
Sign up to set email alerts
|

Instrumentation and design of a frequency-domain diffuse optical tomography imager for breast cancer detection

Abstract: The instrument development and design of a prototype frequency-domain optical imaging device for breast cancer detection is described in detail. This device employs radio-frequency intensity modulated near-infrared light to image quantitatively both the scattering and absorption coefficients of tissue. The functioning components of the system include a laser diode and a photomultiplier tube, which are multiplexed automatically through 32 large core fiber optic bundles using high precision linear translation st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
121
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(122 citation statements)
references
References 36 publications
1
121
0
Order By: Relevance
“…Its main disadvantage remains the low spatial resolution achieved as a result of the highly scattering nature of tissue in the NIR. The resolution of current experimental DOT implementations (25,26) is Ϸ5 mm millimeters, although increased numbers of source-detector pairs and improved signal-to-noise may lead to further resolution improvement.…”
Section: Iffuse Optical Tomography (Dot) In the Near-infrared (Nir)mentioning
confidence: 99%
See 1 more Smart Citation
“…Its main disadvantage remains the low spatial resolution achieved as a result of the highly scattering nature of tissue in the NIR. The resolution of current experimental DOT implementations (25,26) is Ϸ5 mm millimeters, although increased numbers of source-detector pairs and improved signal-to-noise may lead to further resolution improvement.…”
Section: Iffuse Optical Tomography (Dot) In the Near-infrared (Nir)mentioning
confidence: 99%
“…Thus far, DOT images of absorbing and scattering objects embedded in tissue-like media have been produced (2,(25)(26)(27)(28)(29)(30) by using phantoms. The experimental certainty of the phantom contrast makes the evaluation of the technique straightforward.…”
Section: Iffuse Optical Tomography (Dot) In the Near-infrared (Nir)mentioning
confidence: 99%
“…[10][11][12][13][14] Most DOT breast imaging systems used fibers to deliver lasers to breast surface and collected the diffused light on the breast surface, in which the measurement number was determined by the optode pairings. 11,[15][16][17][18][19][20][21][22] To increase the number of measurement data, Culver et al reported a charge coupled device (CCD) camera based DOT imaging system. 23 Turner et al used a CCD camera to measure early photons in a DOT imaging system.…”
Section: Introductionmentioning
confidence: 99%
“…NIRS instruments are of three main types based on the way they transmit signals and analyze the detected signals. 9 The types are continuous wave ͑cw͒, 2,10-16 frequency domain, 17,18 and time domain. 19 The instrument presented in this paper is a cw type instrument.…”
Section: Introductionmentioning
confidence: 99%